Exploring the mechanisms by which common inhalational anesthetics influence malignant tumor metastasis: A data mining study based on comparative toxicogenomic databases - Yiyu Chen; Wenlan Ouyang; Hu Lv; Wei Chen (Ecotoxicology and Environmental Safety)
Surgery remains the primary treatment for solid malignant tumors, but controlling postoperative tumor recurrence and metastasis continues to be a major challenge. Understanding the factors that influence tumor recurrence and metastasis after surgery, as well as the underlying biological mechanisms, is critical. Previous studies suggest that anesthetic agents may increase the risk of tumor recurrence and metastasis in patients with cancer, but the mechanisms underlying these findings remain unclear. In this study, we utilized toxicogenomics and comparative toxicogenomic databases to analyze data and explore the potential mechanisms by which three commonly used inhalational anesthetics—sevoflurane, isoflurane, and halothane—might promote malignant tumor metastasis. The results identified 18 genes that may be associated with tumor metastasis. Functional enrichment analysis revealed that these anesthetics could influence tumor cell migration by activating signaling pathways such as the IL-17 and tumor necrosis factor signaling pathways, thereby potentially inducing tumor metastasis. Moreover, by constructing a TF-mRNA network, we predicted several transcription factors that might play key roles in anesthetic-induced tumor metastasis. The analysis revealed a total of 87 regulatory relationships between transcription factors and mRNA. These findings offer new insights for future in vivo or in vitro studies and contribute to a better understanding of the relationship between inhalational anesthetics and tumor metastasis, providing valuable reference points for clinical decision-making. The results of this study also provide a reference for the determination of subsequent clinical treatment targets. Hence, future laboratory studies should prioritize investigating the specific genes and common mechanisms identified in this study.